Marketing fortified rice: Effects of aspirational messaging and credibility of health claims - Chowdhury, Reajul; Crost, Benjamin; Hoffmann, Vivian (University of California, Berkeley, 2021)
Studies assessing the impact of information on uptake of preventive health products among the poor have shown mixed results, and little is known about what type of messages are most effective. Drawing on insights from the literature on marketing and consumer behavior, we argue that messages which position a product as aspirational or establish the credibility of its health benefits can increase consumer demand for the product. We test the individual and joint impacts of such messages through a field experiment eliciting willingness to pay for fortified rice in Chandpur District, Bangladesh. We find that the combination of these approaches increases the proportion of participants willing to pay a premium at least equal to the cost of fortification by 18 percentage points. In sharp contrast to the existing literature on welfare stigma, we also show that awareness of free distribution of fortified rice through government programs does not negatively affect consumer demand, but rather appears to lend credibility to health claims about the product.